The Value Relevance of Sustainability Reporting: Comparison between Malaysia and Indonesia Stock Market - Nanies Putri Halimah; Alfiana Irsyanti; Lutfi Rohmah Aini (The Indonesian Journal of Accounting Research, 2020)
This study aims to investigate whether information content on sustainability reporting has a significant association with listed companies share price. We also assess the difference effect of sustainability reporting adoption in the mandatory and voluntary context in developing countries, particularly in Malaysia and Indonesia for several reasons provided. The final sample was 43 firms in Indonesia and 57 firms in Malaysia. The data in this study used secondary data obtained from Thomson Reuters Datastream. To examine our hypothesis, we apply regression model. The result of this study provide evidence that information on sustainability reporting has significant association with firm’s price. This shows that sustainability reporting is relevant because it can makes a differences in users decision and is measured reliably enough to be reflected in value of equity. Other result in this study, the value relevance of sustainability reporting is stronger in Malaysian stock market rather than in Indonesian stock market.